"Bond strength of 3d printed acrylic resin with silicone soft liner after ethyl acetate surface treatment (A Review of Literature)" - Yousif Waleed Abd Alrazaq / Bayan Saleem Khalaf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This literature review emphasizes the impact of ethyl acetate organic solvent as surface treatment agent for 3-dimentional (3D) printed polymethyl methacrylate denture base and silicone soft liner on enhancing the strength of bonding of these materials. Over time, Denture soft liner materials have appeared as important components in prosthodontics, offering enhanced comfort, tissue adaptation for denture wearers and restore the inflamed and distorted mucosa. It is commonly agreed that the main drawback is debonding of the lining material from the 3D printed denture base. Therefore, there is a need for enhancing the strength of bonding of these materials.